A classroom game to teach the principles of money and banking - Adam Hoffer (Cogent Economics & Finance, 2015)
This paper describes how to implement and run a game for teaching the principles of money and banking to an undergraduate economics class. The game primarily deals with the market for loanable funds, but numerous extensions are provided to cover topics such as monetary policy, the tools of the Federal Reserve, shifts in the equilibrium of the market for loanable funds, and the quantity theory of money. The experiment can be used in principles, intermediate macroeconomics, or money and banking courses. The experiment takes approximately 45 minutes to run, depending on class size, and requires no computers.
Keywords: A22; C9; E42; 330; money and banking; market for loanable funds; teaching; economics education; games; experiments; economic tools for teaching